Biometric and RFID based authentication system for exam paper leakages detection using IoT technology - J. Ann Roseela; T. Godhavari (Institute of Advanced Engineering and Science, 2020)
Education is the soul of a community; it goes from one generation to another. Exam is the prime responsibility of an educational framework. The reason for an examination is to select talented applicants for multiple positions. Exam is an important aspect of the education system to test students' abilities online and in oral papers. Every year we receive deferred/canceled exam messages due to paper leakage. Therefore, we have come up with a affordable and concise outcome, and we have decided to design and implement the